Efeitos do consumo materno do baru (Dipteryx alata Vog.) sobre a microbiota fecal, parâmetros de estresse oxidativo cerebral e desenvolvimento comportamental da prole de ratas Wistar - Pereira, Diego Elias (2022)
This study evaluated the impact of maternal supplementation with baru oil and almond on the fecal microbiota, brain oxidative stress and behavioral development of the offspring of Wistar rats treated during pregnancy and lactation. The mothers were randomized into three groups: Control (CG) - received distilled water by gavage; Oil – received 2.000 mg of baru oil/kg and Almond - received 2.000 mg of baru almond/kg. After birth, the offspring were standardized into litters of 6 male pups. At the end of lactation, breast milk samples were collected for analysis of the fatty acid profile. In the offspring, evaluation of somatic development and reflex ontogenesis was performed during the first 21 days of life. During adolescence (T45) and adulthood (T90) tests of Habituation to the Open Field (OF) were performed; Object Recognition test (ORT); Morris Water Maze (MWM); Elevated Plus Maze (EPM) and Light-Dark Box (LDB). Fatty acid content and histological analysis of the brain were evaluated at T45 and T90, as well as stool collection for fecal microbiota analysis. Supplementation increased the content of PUFAs in breast milk and in the brain of adolescent and adult offspring, as well as the content of docosahexaenoic and arachidonic acid (p < 0.05). Acceleration of reflex ontogeny and somatic development was observed in the experimental groups (p <0.05). The oil group showed a decrease in the ambulation parameter in the second exposure to OF, at T45. In adulthood, the reduction occurred in both groups (p<0.05). In ORT, the oil and almond groups showed improvement in short and long-term memory at T45. In the adult phase, these results were only evident in the almond group (p<0.05). The experimental groups showed greater ambulation and rearing and reduced grooming behavior and number of fecal bolus, at T45. In the adult phase, there was a higher number of rearing and lower number of fecal bolus only in the almond group (p<0.05). In the EPM, the almond group had the highest number of entries and time spent in the open arms, at T45. The almond group at T90 had a higher number of entries in the open arms when compared to the oil and control groups (p<0.05). In the LDB, a longer time spent by the experimental animals in the light compartment of the box was observed at T45 and T90 (p<0.05). Histological analysis showed that the supplementation preserved the cells of the hippocampus and cortex of the animals in both life stages. There was an increase in glutathione levels and a reduction in MDA in the brain of the oil and almond offspring, at T45. At T90, only the almond group showed high levels of glutathione (p<0.05). The microbial communities of faeces, as well as the metabolic pathways used by intestinal bacteria were significantly different comparing the experimental groups to the control at T45. The results showed the neuroprotective effect of supplementation at different stages of life, which are associated with the impact of PUFAs and antioxidants in the development/protection of the central nervous system, in the remodeling of the gut microbiota, as well as in its production of neuroactive compounds.